Enhancing Community Understanding of Legal Protection: Legal Counseling for Indonesian Migrant Workers in Assisted Villages - Surya Anom; Mas Nana Jumena (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2022)
Law No. 18 of 2017 Concerning the Protection of Indonesian Migrant Workers, in general, provides legal protection for (Indonesian Migrant Workers). Law No. 18 2017 about the Protection of Indonesian Migrant Workers contains regulations pertaining to protecting migrant workers from Indonesia (PMI). Whereas Article 7 stipulates that protection for PMI candidates must be provided in three stages, namely protection prior to, during, and following employment, each of which must involve the state. The two targeted villages of the law department, Pabuaran, and Sindangsari, are the focus of legal community service projects by Abdimas Team International Law Department of Universitas Sultan Ageng Tirtayasa.